Assessing the effects of urban street trees on building cooling energy needs: The role of foliage density and planting pattern. (February 2021) - Tsoka, Stella; Leduc, Thomas; Rodler, Auline
Highlights: A one-way coupling approach between ENVI-met and Energy Plus is established. The cooling potential of common urban trees with different foliage densities is analyzed. The cooling potential of urban street trees is directly related to their foliage density. The shading effect of dense trees can lead to energy savings of 54 % Abstract: This study presents an one-way coupling approach between the ENVI-met microclimate model and the EnergyPlus building energy simulation program, to assess the effect of the urban greenery on the improvement of the buildings' cooling energy needs, in a dense urban area in Thessaloniki, Greece. Three commonly encountered urban tree species with different foliage densities are analyzed, whereas 2 different planting patterns are also considered. The obtained results indicate that the potential of trees on cooling the ambient air temperature and regulating the buildings cooling energy needs is mainly attributed to the radiative shading and the respective reduction of the solar heat gains of the exposed building façades. Moreover, the reduction of the building's cooling energy demand due to the addition of trees is directly related to their foliage density and their planting pattern. The higher energy savings up to 54 % have been achieved when the trees formed a continuous shading canopy and for the Leaf Area Density of 2.5 m 2 /m 3 . Yet, the cooling potential of street trees has been found rather minor when they were not tall enough to shade the biggest part of the outer building façade.